Legal Consequences of a Notarial Deed That Does Not Accord to the Facts And is Not Signed in the Presence of a Notary (Study Decision Number 46/Pdt.G/2023/PN Cbi) - Christy Chandra; Tjempaka (Journal of Law, Politic and Humanities, 2024)
Indonesia has established its country as a rule of law so one of the goals of a rule of law is to create legal certainty in every interaction between society and the state. The agreement made by a notary in a notarial deed is a manifestation of legal certainty. Laws Number 2 of 2014 concerning Amendments to Laws Number 30 of 2004 concerning the Position of Notaries has given authority to notaries to make authentic deeds. One of the problems that often occurs is that the contents of the notarial deed are not by the wishes of the person present and are not signed in the presence of a notary. The purpose of this research is to determine the validity of a deed that was not made according to the wishes of the appeared and was not signed before a Notary and its application in the case of Decision Number 46/Pdt.G/2023/PN Cbi. This research uses normative legal research methods with an approach to legal cases (case study) and statute approach using secondary data types and data collection techniques, namely interviews and document studies, as well as using legal analysis and prescriptive data collection techniques. Based on the results of this research, it is necessary to know that the validity and legal force of a deed that has been made by a Notary but not in the appeared, where the contents of the deed are not per the wishes of the appearer and is not signed in the presence of the Notary, then the action carried out by the Notary is unlawful acts regulated in Article 1365 of the Civil Code so that the person appearing can ask the Notary to be held civilly responsible as in the case in decision Number 46/Pdt/G/2023/PN Cbi..